How C:N:P stoichiometry in soils and plants responds to succession in Robinia pseudoacacia forests on the Loess Plateau, China - Liu, Yang; Fang, Ying; An, Shaoshan (Forest ecology and management, 2020)
•SOC significantly increase and reach a peak at the stand ages of 30–40 years.•N contents in leaf and litter increased with the stand ages.•Robinia pseudoacacia can enhance C and N contents in soils and microbes in the first 30 years.•Robinia pseudoacacia was P-limited and this limitation become increasing along with the forest stand ages. Ecological stoichiometry in plants and soils is an important indicator of element cycling and ecosystem stability that has been used to indicate nutrient limitation. However, the stoichiometric responses of plants and soils along a chronosequence on the Loess Plateau of China has not been studied. In this study, we chose four stand ages (5–10 years old, YF; 10–20 years old, NF; 30 years old, MF; 40–50 years old, OF) of Robinia pseudoacacia and abandoned land (AC) as research subjects to illustrate the C:N:P stoichiometry interactions among soils, plant tissues (green leaves, leaf litter, and roots), and soil microbes. The results demonstrated that the soil organic C, total N, soil microbial biomass C (MBC), microbial biomass N (MBN), and microbial biomass P (MBP) contents increased significantly with afforestation age and reached a peak in the OF stand. The soil C:N ratio showed a significant increase from 9.2 to 13.1, while no significant differences were observed in the soil MBC:MBN ratios. Compared with the R. pseudoacacia forests, AC had the lowest soil C:N, N:P, and C:P ratios. Forest stand age had different influences on the C, N, and P contents in leaves, leaf litter, and fine roots. The most obvious trends were that the N contents in leaves and litter increased with stand age, indicating that old forests could accumulate more N in their leaves and litter. The leaf N:P ratio increased from 16 to 20 along the chronosequence, which demonstrated that P was the limiting element for the growth of R. pseudoacacia plantations on the Loess Plateau. The P demand increased with stand age. Therefore, our results indicated that R. pseudoacacia plantations enhance the C and N contents in soils and microbes in the first 30 years of growth and show an increasing demand for P over time. Therefore, attention should be paid to the application of phosphate fertilizer for the management of R. pseudoacacia plantations.